GEOCHEMICAL FEATURES AND ORE-BEARING OF ULTRABASIC ROCKS OF THE DEVLADOVO MASSIF (MIDDLE PRIDNIPROVYE) - VELIKANOVA, O.; VELIKANOV, Yu. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper deals with geochemical characters and ore perceptivity of ultrabasic rocks of the Devladovo massif. A perspective of the Devladovo massif for discovery of deposits of sulfide nickel, cobalt and copper is suggested.